Self-concept in fairness and rule establishment during a competitive game: a computational approach - Lee, Sang Ho; Kim, Sung-Phil; Cho, Yang Seok (Frontiers in Psychology, 2015)
People consider fairness as well as their own interest when making decisions in economic games. The present study proposes a model that encompasses the self-concept determined by one’s own kindness as a factor of fairness. To observe behavioral patterns that reflect self-concept and fairness, a chicken game experiment was conducted. Behavioral data demonstrates four distinct patterns; ‘switching’, ‘mutual rush’, ‘mutual avoidance’, and ‘unfair’ patterns. Model estimation of chicken game data shows that a model with self-concept predicts those behaviors better than previous models of fairness, suggesting that self-concept indeed affects human behavior in competitive economic games. Moreover, a non-stationary parameter analysis revealed the process of reaching consensus between the players in a game. When the models were fitted to a continuous time window, the parameters of the players in a pair with ‘switching’ and ‘mutual avoidance’ patterns became similar as the game proceeded, suggesting that the players gradually formed a shared rule during the game. In contrast, the difference of parameters between the players in the ‘unfair’ and ‘mutual rush’ patterns did not become stable. The outcomes of the present study showed that people are likely to change their strategy until they reach a mutually beneficial status.